Developing professional identity in post‐professional healthcare students through self‐authorship. (6th December 2021) - Rivera, Matthew J.; Eberman, Lindsey E.; Games, Kenneth E.
Abstract: This article describes the integration of self‐authorship theory to aid post‐professional healthcare students in the continued development of professional identity. Specific teaching and instructional strategies are provided along with curricular development using a self‐authorship framework.